Frequency of Port Site Infection After Laparoscopic Cholecystectomy: Port Site Infection and Laparoscopic Cholecystectomy - Bilawal Khan, Muhammad; Khan, Ajmal; Ahmad Khan, Zakir; Khan, Kamran; Waqas Khan, Muhammad; Rehman, Karishma (Pakistan Journal of Health Sciences, 2022)
Cholangitis is an inflammation of the biliary tree due to Gallstones. The port region is susceptible to postoperative infections when a patient has excessive wounding and a microorganisms isolated from spontaneously procured tissue or fluid inside the upper cut. Objectives: To analyze the frequency of port site infection (PSI) and to assess variables influencing PSI following laparoscopic cholecystectomies. Methods: This research was carried during 2022 in two hospitals in Peshawar(Pakistan). Only 55 of the 907 patients who had PSI after going through LC surgeries were included and were kept under observations for six months. Data were collected by questionnaire, imported into the SPSS for statistical analysis. Descriptive statistics and Chi-square test were used for association between variables. Results: 34 patients out of 55 had CC, whereas 21 patients underwent surgery following an AC and became infected. Following LC, PSI frequency were lower than after open cholecystectomy. Majority of patients were women. Only five patients, based on the PSI, got an infection at the lateral ports, whereas 11 patients and 39 patients respectively, developed infections at the umbilical and epigastric ports. PSI came from majority of the female patients showing a significant association in frequency of PSI in relation to gender. Conclusion: Females tend to have high PSI rates and frequent epigastric port PSIs.